Ibrutinib for central nervous system lymphoma: the Australasian Lymphoma Alliance/MD Anderson Cancer Center experience. (16th July 2020) - Lewis, Katharine L.; Chin, Collin K.; Manos, Kate; Casey, John; Hamad, Nada; Crawford, Julie; Ho, Shir‐Jing; Issa, Samar; Grigg, Andrew; Wood, Peter; Gandhi, Maher K.; Do, Bryan; et al.
Summary: Primary and secondary central nervous system lymphomas (PCNSL/SCNSL) are aggressive rare malignancies with dismal outcomes. Encouraging data have emerged from Phase I/II clinical trials treating relapsed/refractory PCNSL/SCNSL with ibrutinib. We analysed 33 patients who received ibrutinib, alone or with other therapies, for PCNSL ( n  = 9) or SCNSL ( n  = 24). The objective response rate was 58% (complete response 55%). The median progression‐free survival and overall survival for patients with PCNSL were both 3·1 months; for SCNSL, 10·2 and 11·5 months respectively. Only one invasive fungal infection was observed, despite concurrent or recent use of dexamethasone 8–16 mg daily in 14 patients (42%). Ibrutinib has encouraging activity in these aggressive malignancies.